2011
DOI: 10.1007/s13244-011-0101-8
|View full text |Cite
|
Sign up to set email alerts
|

The emerging role of magnetic resonance imaging and multidetector computed tomography in the diagnosis of dilated cardiomyopathy

Abstract: Magnetic resonance imaging and multidetector computed tomography are new imaging methods that have much to offer clinicians caring for patients with dilated cardiomyopathy. In this article we briefly describe the clinical, pathophysiological and histological aspects of dilated cardiomyopathy. Then we discuss in detail the use of both imaging methods for measurement of chamber size, global and regional function, for myocardial tissue characterisation, including myocardial viability assessment, and determination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 101 publications
0
5
0
Order By: Relevance
“…Genetic inheritance is likely to play a role in the development of the disease in 20 to 35% of patients, but also acquired conditions such as metabolic abnormalities, inflammatory and infectious processes, neuromuscular diseases and a large variety of cardiotoxic agents (chemotherapeutic agents, alcohol, illicit drugs) can lead to DCM (Slavich et al, 2011). DCM onset is slow and can appear at any age, with most patients being 30 to 50 years old.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic inheritance is likely to play a role in the development of the disease in 20 to 35% of patients, but also acquired conditions such as metabolic abnormalities, inflammatory and infectious processes, neuromuscular diseases and a large variety of cardiotoxic agents (chemotherapeutic agents, alcohol, illicit drugs) can lead to DCM (Slavich et al, 2011). DCM onset is slow and can appear at any age, with most patients being 30 to 50 years old.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that CCTA can also identify prognostically important nonobstructive CAD, such as vascular spasm angina ( 28 , 29 ). CCTA is becoming a frontline strategy for chest pain patients and has been applied in the diagnosis of dilated cardiomyopathy ( 30 , 31 ). CCTA might be used in conjunction with echocardiography to exclude cardiac sarcoidosis.…”
Section: Discussionmentioning
confidence: 99%
“…Chamber enlargement is the first compensatory step aiming to maintain an appropriate stroke volume (SV) as shown by the Frank–Starling mechanism. 7 Above a critical sarcomere stretch, the efficiency of interaction between actin and myosin filaments decreases, causing eccentric ventricular hypertrophy, with decreased wall thickness to chamber diameter ratio and increased ventricular sphericity resulting in impairment of SV. These changes cause an increase in myocardial wall stress with increased oxygen demand and subsequent worsening of the LV systolic performance.…”
Section: Discussionmentioning
confidence: 99%
“…The LV enlargement further dilates the mitral valve ring, dislocates the papillary muscles, and impairs leaflet coaptation thereby causing mitral valvular regurgitation and putting additional volume load on the already dilated ventricle. 7 This in turn will lead to further lowering of EF by compounding the failure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation